Parental occupational exposure to solvents and heavy metals and risk of developing testicular germ cell tumors in sons (NORD-TEST Denmark) - Ann Olsson; Kayo Togawa; Joachim Schüz; Charlotte Le Cornet; Béatrice Fervers; Susanne Oksbjerg Dalton; Eero Pukkala; Maria Feychting; Niels Erik Skakkebæk; Johnni Hansen (Nordic Association of Occupational Safety and Health (NOROSH), 2018)
OBJECTIVE: The present study aims to assess if parental occupational exposure to solvents or heavy metals is associated with risk of testicular germ cell tumors (TGCT) in sons in Denmark. METHODS: The NORD-TEST Denmark included 3421 cases diagnosed with TGCT at ages 14-49 years in Denmark between 1981 and 2014. Controls (N=14 024) selected from the central population registry were matched to cases on birth year. The Danish Supplementary Pension Fund provided parental occupational information. A job-exposure matrix was used to assign exposures, and conditional logistic regression models were used to estimate odds ratios (OR) and 95% confidence intervals (CI). RESULTS: The overall analyses showed no significant associations except for paternal exposure to a sub-group of "heavy metal(s) and solvent(s)" (OR 1.50, 95% CI 1.01-2.24). Most fathers in this category had worked in wood related jobs and were assigned exposure to chromium VI and toluene. Other sub-group analyses suggested that maternal exposure to aromatic hydrocarbon were associated with TGCT risk, in sons born in 1970-1979, and to heavy metals (chromium, iron and nickel) in sons born in 1980-1998. CONCLUSION: NORD-TEST Denmark provides no strong support for an association between parental exposures to solvents or heavy metals and TGCT in sons, and only weak support for an association between paternal exposure to chromium and toluene and TGCT risk in sons.